2006
DOI: 10.1093/eurheartj/ehl093
|View full text |Cite
|
Sign up to set email alerts
|

Substrate modification combined with pulmonary vein isolation improves outcome of catheter ablation in patients with persistent atrial fibrillation: a prospective randomized comparison

Abstract: PVI alone is insufficient in the treatment of persistent AF. However, additional left linear lesions increase the success rate significantly. Early AF-relapses are associated with a negative outcome after PVI alone but not following additional SM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
233
0
11

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 277 publications
(250 citation statements)
references
References 39 publications
6
233
0
11
Order By: Relevance
“…5,8,10 Furthermore, additional linear ablation demonstrated better clinical outcomes in another 3 randomized trials. 6,7,12 Nonetheless, results of other trials did not show a clinical benefit of additional CFAE ablation, 4,9 and the recently published STAR AF II trial revealed no difference in clinical outcomes when comparing stand-alone PVI to PVI plus additional CFAE or linear ablation in a large cohort of patients with persistent AF. 13 The stepwise ablation approach was first investigated by Haïssaguerre et al 15 and consisted of the sequential combination of PVI and additional ablation of CFAEs and, in case of conversion to AT during the ablation procedure, linear ablation; in that original study, 95% of patients were in SR after 1 year and multiple ablation procedures.…”
Section: Current Ablation Strategies For Chronic Afmentioning
confidence: 96%
See 1 more Smart Citation
“…5,8,10 Furthermore, additional linear ablation demonstrated better clinical outcomes in another 3 randomized trials. 6,7,12 Nonetheless, results of other trials did not show a clinical benefit of additional CFAE ablation, 4,9 and the recently published STAR AF II trial revealed no difference in clinical outcomes when comparing stand-alone PVI to PVI plus additional CFAE or linear ablation in a large cohort of patients with persistent AF. 13 The stepwise ablation approach was first investigated by Haïssaguerre et al 15 and consisted of the sequential combination of PVI and additional ablation of CFAEs and, in case of conversion to AT during the ablation procedure, linear ablation; in that original study, 95% of patients were in SR after 1 year and multiple ablation procedures.…”
Section: Current Ablation Strategies For Chronic Afmentioning
confidence: 96%
“…3 The optimal strategy for persistent AF is not known, and previous studies investigating more extensive ablation strategies in addition to PVI demonstrated heterogeneous results. [4][5][6][7][8][9][10][11][12] The recently published STAR AF 2 trial (Substrate and Trigger Ablation for Reduction of Atrial Fibrillation Trial) compared initial stand-alone PVI to PVI with additional ablation of complex fractionated atrial electrograms (CFAEs) or additional linear ablation and could not demonstrate a superior outcome for the additional ablation strategies. 13 The prospective and randomized Alster-Lost-AF © 2017 American Heart Association, Inc.…”
mentioning
confidence: 99%
“…Linear ablation of mitral isthmus between the mitral annulus and the left inferior PV can significantly modify AF substrate [53]. Completeness and transmurality of linear lesions are very important for the successful treatment of AF as well as for the prevention of iatrogenic atrial tachycardia after ablation [54]. Linear ablation leads to compartmentalization of the LA and reduction of the area with CFAE, thus resulting in an additional AF cycle length increase, which can be critical for the AF termination during a stepwise approach to the ablation of longstanding persistent AF [55].…”
Section: Figure 2 Catheter Ablation Of Paroxysmal Af: Elimination Ofmentioning
confidence: 99%
“…However, circumferential antral PV isolation, particularly if it is combined with additional modification of AF substrate, whether by the linear LA ablation and/or CFAE ablation, may lead to the occurrence of atrial tachycardia in 7.6%-44% of patients [24,42,54,[194][195][196]. After usage of similar ablative strategy (CFAE + PVI), post-procedural incidence of atrial tachycardia was remarkably higher after the ablation of persistent AF than after the ablation of paroxysmal AF (20.0% vs. 2.4%) [197].…”
Section: Phrenic Nerve Injurymentioning
confidence: 99%
“…1,30) This discrimination also enables evaluation of catheter ablation efficacy as well as the necessity of additional procedures for standard pulmonary vein isolation, ie, linear ablation, continuous fractionated atrial electrogram ablation, and/or ganglionated plexi ablation. 1,4,31,32) Additionally, because the discrimination of PAF and persistent AF patients in the present study population was in "new-onset AF" patients, the present results are applicable for "first documented AF" patients. To the best of our knowledge, this is the first report which stated the parameters to discriminate between PAF and persistent AF patients in cases with "new-onset" AF.…”
Section: Parameters To Discriminate Between Paf and Persistent Afmentioning
confidence: 79%